Application of Satir Growth Model for personal growth and professional development among counselors in Malaysia - Chin, Choon Moy (2013)
Professional development focus in counseling theories and skill proficiencies, and personal growth development focus on self awareness and wellness has been widespread to make an effective counselor. This prompted the needs to explore a suitable approach to achieve this objective. Few literatures using qualitative methodology revealed the learning of Satir Growth Models psycho-education was an effective tool to improve personal growth and professional development. The purpose of this study was to explore how Satir Growth Model’s psycho-education is able to expedite counselors’ personal growth and professional development in Malaysia. FOUR informants’ life changes experiences were solicited through semi-structured interviews using basic qualitative research approach, which resulted in the emergence of three themes: ‘‘humanity awakening’’, “therapeutic competency”, and “self-care commitment”. The findings showed that the informants’ main driving force to seek personal growth and professional effectiveness was the counselors' own humanity calling and positive transformation in personal life. These resulted counselors were better equipped with therapeutic competency attributes such as enhanced sensitivity, assessment capability, congruence communications, enabling the use of Self, using a systemic and therapeutic framework to direct both oneself and clients towards a positive directional goals. The findings were found to be consistent with a number of other studies, which suggest that personal growth is an integral part of professional development, whereas personal wellness is an essential commitment by the counselors for their own personal health and professional longevity. Overall, the study aims to progress towards a practical developmental framework to effectively deliver an integrated personal growth and professional development program in the training of counselors and a future research program.